Penguatan Karakter Peduli Lingkungan di Sekolah Dasar Melalui Karya Seni Ecoprint - Arief Setyo Nugroho; Bambang Sumardjoko; Anatri Desstya (Elementary Teacher Education Program, Majalengka University, 2023)
Technological developments have an impact on decreasing environmental quality. Activities carried out by humans during their lifetime directly or indirectly affect their environment, the condition of the plants in the school garden looks less maintained, food and beverage packaging waste is left scattered. Many studies on strengthening the character of caring for the environment are still limited to the substance of learning and school cleaning activities. The purpose of this study was to explore the results of strengthening the character of caring for the environment through ecoprint artwork in elementary schools. Through a qualitative descriptive approach, it is expected to be able to reveal the problems in this study. The need for data collection, the types of instruments used are interviews and observations. Researchers use triangulation techniques and sources to test the validity of the data. This research was conducted using interactive data analysis techniques. Based on the results of research on the implementation of strengthening the character of caring for the environment through ecoprint artwork in elementary schools, the following are as follows: (1) The character of caring for the environment, the indicator of not using harmful synthetic dyes, reaches 100%. (2) Caring for the environment, the indicator of reducing the use of toxic chemicals reached 66.6%. (3) Caring for the environment Characteristics of saving energy and water is 100%. (4) Caring for the environment Characteristics of caring for and caring for plants is 100%. (5) Caring for the environment Characteristics of reduce, reuse and recycle indicators reached 75%. In general, it can be concluded that strengthening the character of caring for the environment through ecoprint artwork achieves a success percentage of 88.32%. Apart from the main goal of strengthening the character of caring for the environment, it has another impact, namely being able to awaken the entrepreneurial spirit of students by producing paintings and cloth products with leaf motifs that can have economic selling value..